2013
DOI: 10.1097/ccm.0b013e31827ca960
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Chemiluminescent Intensity in Response to Lipopolysaccharide Assessed by Endotoxin Activity Assay on Admission Day Predicts Mortality in Patients With Sepsis*

Abstract: Maximal chemiluminescent intensity level measured on admission day appears to have high predictive value for mortality in patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Sepsis was defined as a systemic response to an infection including the criteria for SIRS plus microbiological evidence of a focal infection and/or a positive blood culture. Septic shock was defined as sepsis-induced hypotension, persisting despite adequate fluid resuscitation, along with the presence of hypoperfusion abnormalities or organ dysfunction [ 35 ]. Patients were considered to suffer from SIRS if they met the criteria defined in the guidelines of the American College of Chest Physicians/Society of Critical Care Medicine [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sepsis was defined as a systemic response to an infection including the criteria for SIRS plus microbiological evidence of a focal infection and/or a positive blood culture. Septic shock was defined as sepsis-induced hypotension, persisting despite adequate fluid resuscitation, along with the presence of hypoperfusion abnormalities or organ dysfunction [ 35 ]. Patients were considered to suffer from SIRS if they met the criteria defined in the guidelines of the American College of Chest Physicians/Society of Critical Care Medicine [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Reduced oxidative activity may be associated with immune dysfunction and high mortality [ 25 , 26 ]. Kiguchi et al [ 18 ] reported that CI max before commencing treatment is indicative of the maximum neutrophil activity in whole blood and is highly predictive of mortality in patients with sepsis. CI max reflects neutrophil vitality or fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting respiratory burst was detected by a chemiluminometer (Autolumat LB953; Berthold Technologies GmbH & Co. KG, Bad Wildbad, Germany) as light released from the lumiphore luminol. The maximum stimulated response (termed as CI max by Kiguchi et al [ 18 ]) was measured using lipopolysaccharide (4.6 ng/mL) as the stimulant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations